2013
DOI: 10.5539/apr.v5n1p28
|View full text |Cite
|
Sign up to set email alerts
|

The Questionable Existence of Gravitomagnetic Force

Abstract: Using a simple model of moving massive parallel plates this paper explains that there cannot be any gravitomagnetic force contrary to a widely spread belief that such a force exists. The existence of this force is usually supported by the analogy with the Maxwell theory of Electromagnetic fields. The gravitomagnetic force, analogous to a force described by the Lorentz force equation, and the accompanied gravitoelectromagnetic field equations, are all derived from Einstein field equations by linearization for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…
AbstractIt has been shown in an earlier publication (Hynecek, 2013) that the frame dragging effect due to the Earth's rotation, which is claimed that the Gravity Probe B (GP-B) has detected, cannot exist. In this paper it is shown that the Geodetic Precession, which the GP-B has also measured, and is typically calculated from the Einstein's General Relativity Theory (GRT), can also be calculated from a different metric.
…”
mentioning
confidence: 99%
“…
AbstractIt has been shown in an earlier publication (Hynecek, 2013) that the frame dragging effect due to the Earth's rotation, which is claimed that the Gravity Probe B (GP-B) has detected, cannot exist. In this paper it is shown that the Geodetic Precession, which the GP-B has also measured, and is typically calculated from the Einstein's General Relativity Theory (GRT), can also be calculated from a different metric.
…”
mentioning
confidence: 99%